Pengembangan Aplikasi Helpdesk IT Berbasis Web dengan Integrasi Inventaris dan Logbook di RSUD Gambiran - Moh. Teguh Purwanto; Rini Indriati; Arie Nugroho (Management of Information System Journal, 2026)
At RSUD Gambiran Kediri City, the coordination of IT issue resolution has long relied on informal communication via telephone calls and WhatsApp messages, resulting in incomplete incident reports, difficulties in tracking resolution status, and a lack of service documentation trails. This condition risks directly hindering the quality of healthcare services, as disruptions to information technology infrastructure affect all hospital work units. To address these issues, this study developed a web-based IT helpdesk information system designed to integrate directly with the hospital’s existing inventory and logbook applications. The development process adopted the Waterfall model through four sequential phases: requirements analysis, design, implementation, and testing. Requirements data were gathered through interviews, field observations, and questionnaires distributed to IT officers and relevant department heads. The technology stack utilizes PHP Laravel as the primary framework, MySQL for database management, and Bootstrap for the user interface, hosted on an Ubuntu server running inside an LXC container on the Proxmox virtualization platform. Key features include a six-stage tiered complaint handling workflow, real-time notifications via Telegram, and API connections to the inventory and logbook applications. Functional verification was conducted using Black Box Testing across 14 manual scenarios, 63 feature tests, and 4 unit tests, all of which passed. A feasibility assessment by three respondents through User Acceptance Testing demonstrated full acceptance of all tested features. A satisfaction questionnaire distributed to ten IT officers yielded an average score of 4.6 out of 5. The resulting system successfully replaced previous informal reporting patterns while enhancing organization, response time, and information transparency in managing hospital IT complaints